The illegal mining plundering the entrails of the earth (2014)
This article presents the results of a thesis in social work about the perceptions and effects of illegal alluvial mining in the Cotuhé River (north of the Amazon Trapeze, Colombian Amazon). It presents information about the perceptions on Tikuna Indians of the community of Caña Brava about the meaning of the territory, the arrival of the miners to the Cotuhé River, the environmental and social effects of the mining activity, the impotence of the indigenous organizations, and the abandonment by the State authorities. The community perceives mining in two contradictory manners. On the one hand, some people understand it as a boom that exploits their natural resources not leaving in exchange any economic benefit to the community and causing severe social and environmental damages. On the other hand, some others, mostly the youngsters, perceive it as an economic opportunity to the community. The mining activity has caused a rupture among the community members, and the toxic substances employed by the miners dangerously expose the inhabitants because of the consumption of fish, which is their primary source of protein.